2023
DOI: 10.1007/s00194-022-00602-z
|View full text |Cite
|
Sign up to set email alerts
|

Eineinhalb Jahre E-Scooter – Zwischenbilanz in Hamburg

Abstract: Zusammenfassung Hintergrund Seit der Verbreitung der sog. Elektro-Scooter durch Verleihservices in Hamburg ab Juni 2019 sind Unfälle durch die Nutzung dieser Fortbewegungsmittel regelmäßig registriert worden. Die häufigsten Verletzungsmuster bei verunfallten E‑Scooter-Fahrern betrafen die obere Extremität und den Kopf. Es zeigte sich dabei eine relevante Anhäufung alkoholisierter Fahrer unter den verletzten Personen. Ziel der Arbeit Ziel der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…We found the most common ESA cases were observed (n=12, 35,2%) in summer. Our results are consistent with previous studies that have reported a higher occurrence of ESA during the nighttime and in the summer (8,15,16).…”
Section: Discussionsupporting
confidence: 94%
“…We found the most common ESA cases were observed (n=12, 35,2%) in summer. Our results are consistent with previous studies that have reported a higher occurrence of ESA during the nighttime and in the summer (8,15,16).…”
Section: Discussionsupporting
confidence: 94%